Characterisation of Ternary Complex Formation Between [RuIII(edta)]– and Various Bidentate Ligands12. Issue 8 (24th May 2013) - Jakusch, Tamás; Kiss, Tamás
Abstract Speciations of ruthenium(III)‐edta complexes of bidentate (O, O) (N, O) and (S, O) donor type ligands were determined by pH‐potentiometry and UV/Vis spectrophotometry in aqueous solution. Complexes of [RuIII(edtaHx)L]2– (x = 0, 1, 2 and 3) stoichiometry were only formed and the fully deprotonated species dominate at the physiological pH 7.4. Protonation occurs at the free carboxylate arms of edta; when x = 3 one of the coordination positions of the RuIII becomes free. Formation of protonated ternary complexes are more characteristic for ligands with (N, O) and (S, O) donor sets where the complex formation started (ligands with (N, O) donor set) or completed (ligands with (S, O) donor set) already at pH 2. In acidic conditions the stability order of the complexes follows the (O, O) < (N, O) < (S, O) sequence, which changes slightly for the physiological pH 7.4: (O, O) ≈ (N, O) < (S, O). The complexes formed were characterised also by LNT EPR spectroscopy. The kinetics of the ligand exchange between ternary complexes at pH 6 was found to be dissociative. The reaction rate follows basically the stability order: (O, O) < (N, O) < (S, O). No side reactions were found when the ligands replaced had (O, O) donor set; but formation of [RuIII(edta)(L1), (L2)]3– was hypothesised in the case of ligands with (N, O) or (S, O) donor sets.